A Feasibility Study of Silkworm (Tubifex Sp.) Cultivation Business Using Multilevel Containers with Semi Closed Recirculating System (SCRS) for Community Welfare - Erfan Effendi; Tengku Said Muhammad Farid (Budapest International Research and Critics University, 2021)
Tubifex sp is a natural food for the cultivation of freshwater and ornamental fish in the hatchery phase. The availability of these worms in Pekanbaru City is fluctuating due to the condition of the river volume. Preliminary studies have been conducted to determine the needs of fish cultivators for Tubifex sp and its market value. These studies indicated that Tubifex sp's demand is approximately 2000 liters/month, with a limited supply of only 600 liters/month or 30% out of 100% of the total demand. Furthermore, a survey was also carried out to determine factors responsible for the inadequate supply of Tubifex sp. The results showed that the limited supply was due to (1) the availability of few farmer groups and (2) lack of cultivators. Based on these conditions, Tubifex sp was first cultivated by farmers in an unused sewer. The result showed, (1) sewer water easily permeates these worms, (2) Tubifex sp is attacked by pests, (3) it is difficult to maintain the Tubifex sp environment, (4) there is no production. Therefore, based on these conditions, this research was carried out to cultivate Tubifex sp using a multilevel container with a semi-closed recirculating modern system, as well as ph and water sensors connected to smartphones to maintain the cultivation environment. The results showed that (1) pest attack reduced by 95%, (2) there is an efficient use of water and raw materials, (3) easy environmental conditions to maintain Tubifex sp, (4) amount of production can be controlled, (5) efficient land use, and (6) the worms can be developed on a commercial scale.